Penyalahgunaan Dalam Pemanfaatan Teknologi Informasi Dan Komunikasi Sebagai Sarana Penyebaran Kejahatan Asusila - Ayu, Indah Putri; Pura, Margo Hadi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The rise of crimes such as those that occur in social media assistance has a bad impact on most internet users. As we know nowadays pornographic content is difficult to access. Considering that internet users are not only adults, but also children, this is very proud. Then not only that, many have abused technological advances as a means of prostitution. With this, of course, there needs to be someone who oversees the application of the technology. Indonesia is a state of law, of course, this does not escape the legal arrangements in Indonesia. Therefore, judging from the current phenomena, this journal looks at the phenomena that injure the norms and rules that exist in Indonesia from a legal perspective.